Review of item items of the scale of gratitude in the perspective of Islamic Psychology - Ahmad Muhammad Diponegoro; Yuzarion Yuzarion (Universitas Ahmad Dahlan, 2022)
Diversity is an important study and talk in various religions, and the latter in psychology. Gratitude talks in psychology are related to mental health, social psychology, clinical psychology, educational psychology and especially positive psychology. Talk and research on diversity has been going on for more than two decades. in the study of psychology in general. To be grateful is to present to oneself an oral expression in the form of praise to the khalik for all the favors obtained.